2021
DOI: 10.48550/arxiv.2110.13167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The CGM$^2$ Survey: Circumgalactic O VI from dwarf to massive star-forming galaxies

K. Tchernyshyov,
J. K. Werk,
M. C. Wilde
et al.

Abstract: We combine 126 new galaxy-O VI absorber pairs from the CGM 2 survey with 123 pairs drawn from the literature to examine the simultaneous dependence of the column density of O VI absorbers (N O VI ) on galaxy stellar mass, star formation rate, and impact parameter. The combined sample consists of 249 galaxy-O VI absorber pairs covering z = 0-0.6, with host galaxy stellar masses M * = 10 7.8 -10 11.2 M and galaxy-absorber impact parameters R ⊥ = 0-400 proper kiloparsecs. In this work, we focus on the variation o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 75 publications
(151 reference statements)
0
7
0
Order By: Relevance
“…11 This N OVI is a factor of a few lower than the median column for L * galaxies (Tumlinson et al 2011;Werk et al 2014), and as shown in equation ( 11), the emission scales linearly with the O vi and total gas density column. In fact our estimates may have wider applicability as columns of N OVI = 10 14−15 cm −2 are observed for star forming galaxies over a broad range in stellar mass (Tchernyshyov et al 2021). With this normalization, we have checked that the columns associated with other ions in all of our P (T ) models are likely below measured values; the columns that are observed from absorption studies in other ions would be associated with a pile-up of gas at the equilibrium temperature of ∼ 10 4 K, gas which does not emit substantially in the UV.…”
Section: Uv Lines From Intermediate Temperature Gasmentioning
confidence: 79%
“…11 This N OVI is a factor of a few lower than the median column for L * galaxies (Tumlinson et al 2011;Werk et al 2014), and as shown in equation ( 11), the emission scales linearly with the O vi and total gas density column. In fact our estimates may have wider applicability as columns of N OVI = 10 14−15 cm −2 are observed for star forming galaxies over a broad range in stellar mass (Tchernyshyov et al 2021). With this normalization, we have checked that the columns associated with other ions in all of our P (T ) models are likely below measured values; the columns that are observed from absorption studies in other ions would be associated with a pile-up of gas at the equilibrium temperature of ∼ 10 4 K, gas which does not emit substantially in the UV.…”
Section: Uv Lines From Intermediate Temperature Gasmentioning
confidence: 79%
“…The 𝑥 o characterizes the scale where the slope (defined by 𝛼) changes and both functions are comparable and contribute significantly to the observed distributions. Note that similar functional form (including redshift dependence, with 5-6 parameters) has been used to characterize Mg and O absorber properties around passive and star-forming galaxies from the DESI legacy imaging survey (Lan 2020) and COS-Halos and COS-Dwarfs surveys (Tchernyshyov et al 2021).…”
Section: Covering Fractionsmentioning
confidence: 99%
“…A value of log(sSFR) = −11 often defines the boundary (at 𝑧 = 0) below which galaxies are classified as passive, while galaxies above this limit are considered star-forming. A similar cut was applied by Werk et al (2012) in COS-Halos survey, though other studies may use slightly different cuts for this purpose (Donnari et al 2019), e.g, a higher cut, log(sSFR) = −10 was applied by Tchernyshyov et al (2021) in CGM 2 survey galaxies.…”
Section: Connecting Galaxies With Clustersmentioning
confidence: 99%
See 2 more Smart Citations